Evliyâ Çelebi's Strange and Wondrous Europe - Yeliz Özay (Cahiers Balkaniques)
The Seyahatnâme is an extraordinary source for literary and cultural studies, not just because of its size but also because it includes a wide range of narrative styles and discourses. Evliyâ himself draws our attention to some narratives in particular; one such genre, in which literary taste pushes the limits of imagination of both narrator and reader, is that of marvels and wonders. These parts while they seem to be digressions, have a long-standing history and a function in the tradition of travel narratives. In fact, without considering the Seyahatnâme within its cultural context, we cannot establish, in the text, the difference between the natural and the supernatural, truth and untruth, reality and fantasy. When it comes to marvels and wonders, it is not necessary to mark any boundaries separating the real from the imaginative in order to be able to take these texts seriously. Considering the diversity of the themes and forms grouped under this title, each individual narration needs to be analyzed in a different way depending on its own context.